The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1073/pnas.1217059110
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol growth in Titan’s ionosphere

Abstract: Photochemically produced aerosols are common among the atmospheres of our solar system and beyond. Observations and models have shown that photochemical aerosols have direct consequences on atmospheric properties as well as important astrobiological ramifications, but the mechanisms involved in their formation remain unclear. Here we show that the formation of aerosols in Titan's upper atmosphere is directly related to ion processes, and we provide a complete interpretation of observed mass spectra by the Cass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 46 publications
2
134
3
Order By: Relevance
“…However, it should be noted that we rely on a parameterization of haze production using haze precursors to arrive at our estimated production rates, and that the actual chemical pathways leading to haze formation are as yet poorly understood (see Hörst 2017, for a review). For example, both models (e.g., Lavvas et al 2013) and observations (Coates et al 2007;Crary et al 2009;Liang et al 2007;Wahlund et al 2009;Waite et al 2007) of Titan's atmosphere indicate that ion chemistry plays an important role in haze formation; our photochemical model lacks ion chemistry, and therefore our haze formation picture is incomplete. Laboratory experiments investigating the chemical precursors, pathways, and energy sources that lead to Titan-like hazes and their resulting composition (Cable et al 2012;Hörst & Tolbert 2013;Hörst et al 2017;Imanaka & Smith 2010;Trainer et al 2013;Sciamma-O'Brien et al 2014) are critical to improving our understanding of the formation of exoplanetary hazes, including its dependence on external factors like stellar forcing.…”
Section: Discussionmentioning
confidence: 96%
“…However, it should be noted that we rely on a parameterization of haze production using haze precursors to arrive at our estimated production rates, and that the actual chemical pathways leading to haze formation are as yet poorly understood (see Hörst 2017, for a review). For example, both models (e.g., Lavvas et al 2013) and observations (Coates et al 2007;Crary et al 2009;Liang et al 2007;Wahlund et al 2009;Waite et al 2007) of Titan's atmosphere indicate that ion chemistry plays an important role in haze formation; our photochemical model lacks ion chemistry, and therefore our haze formation picture is incomplete. Laboratory experiments investigating the chemical precursors, pathways, and energy sources that lead to Titan-like hazes and their resulting composition (Cable et al 2012;Hörst & Tolbert 2013;Hörst et al 2017;Imanaka & Smith 2010;Trainer et al 2013;Sciamma-O'Brien et al 2014) are critical to improving our understanding of the formation of exoplanetary hazes, including its dependence on external factors like stellar forcing.…”
Section: Discussionmentioning
confidence: 96%
“…Remarkably, Titan is the only satellite in the Solar System known to display a dense atmosphere [1], harbouring several organic compounds and This irradiation triggers the dissociation and ionization of the simple primordial molecules and subsequently leads, through a series of chemical and physical 20 processes, to the formation of charged aerosol particles with an average mass of 500 Da [8] at altitudes between 950 and 1150 km (upper atmosphere) [6,7,9,10,11]. With decreasing altitude, these particles grow spherically until they reach the detached haze layer at 520 km in Titan's mesosphere, from where they start to form fractal aggregates [7,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The Cassini mission has revealed a chemically complex ionosphere around Titan. N 2 and CH 4 are ionized and/or dissociated by solar photons or particle irradiation marking the onset of a chain of chemical reactions, which produce hydrocarbon and nitrile ions, heavy positive and negative ions, and eventually aerosols (e.g., Vuitton et al, 2007;Waite et al, 2007;Wahlund et al, 2009;Crary et al, 2009;Ågren et al, 2012;Shebanits et al, 2013;Lavvas et al, 2013;Wellbrock et al, 2013). However, Titan dayside ionospheric models have shown difficulties in reproducing observed electron number densities (e.g., Vigren et al, 2013), as well as the observed number densities of HCNH + , the dominant ion in the main ionosphere (e.g., Vuitton et al, 2009;Westlake et al, 2012).…”
Section: Introductionmentioning
confidence: 99%